Commercial banks in the Eastern territories of the Second Polish Republic - Morawski, Wojciech (Acta Archaeologica Lodziensia, 2018)
During the times of Second Polish Republic commercial banking was gradually losing its importance. In the Eastern Borderlands the process ran deeper and faster than elsewhere. In the wake of two consecutive banking crises in 1925 and 1931, a number of weak institutions which had been founded during the period of inflation collapsed. Old banks of Vilnius, founded before 1914, remained relatively strong. Banks of Lvov had played an important role in the 1920’s but became much less important a decade later. One reason was that due to their interaction with the Austrian monetary market, they suffered gravely from the crisis. Shifting of the most important institutions from Lvov to Warsaw did not help, either.